PERAN PETUGAS PENGENDALI PELAYANAN MEDIS (P3M) TERHADAP LENGTH OF STAY (LOS) PASIEN DI IGD RS AKADEMIK UGM - Febriana Prananingrum; Humaera Elphananing Tyas; Firda Ridhayanti; Yanuarta Sulistiyawati (Journal of Health Service Management, 2025)
Background: Overcrowding in Emergency Departments (ED) poses complex challenges, notably regarding patient waiting times or Length of Stay (LOS). The Emergency Flow Coordinator (EFC) at UGM Academic Hospital plays a critical role in regulating patient flow in the ED, yet their specific impact on reducing LOS remains insufficiently defined. Objective: The aim of this study is to determine the impact of the role of EFC on the Length of Stay (LOS) in the Emergency Department of UGM Academic Hospital Methods: A cross-sectional study employing structured questionnaires assessed the EFC's function in the ED, gathering responses from all medical personnel (nurses and physicians) on duty. Analysis of secondary data on patient LOS before (from October 2022 to January 2023) and after (from February 2023 to January 2024) EFC implementation was conducted. Results: According to the Director's Decree of UGM Academic Hospital, the majority of the respondents 90% (45) who assessed EFC (11) considered that EFC plays a very important role in carrying out their job descriptions. From registration to inpatient admission, the average duration of patients in the ED was recorded at 190 minutes (n=9805), which was a decrease of 17.21% from the duration before EFC, which was 229.5 minutes (n=472). The Wilcoxon sum-rank test was used to analyze the difference in LOS between before and after the EFC policy was implemented. The p-value was 0.001, indicating statistical significance. Conclusions: The EFC is essential in fulfilling its duties, as evidenced by a significant reduction in ED patient LOS following its implementation, enhancing the efficiency of care delivery.